ALOS-derived glacier and rock glacier inventory of the Volcán Domuyo region (~36° S), southernmost Central Andes, Argentina - Falaschi, Daniel; Masiokas, Mariano Hugo; Tadono, Takeo; Couvreux, Fleur (Zeitschrift für Geomorphologie)
In this study we use optical ALOS AVNIR-2 and PRISM satellite images to map and inventory glaciers as well as active, inactive and fossil rock glaciers in the Volcán Domuyo region (36°16' S-36°54' S), located in the northwestern tip of the Neuquén Province in Argentina. The area is termed "Transition Cordillera" since it lies between the southernmost reaches of the Central Andes and the Patagonian Andes. We inventoried a total of 106 glaciers, covering an area of ~25.4 km2, and 173 intact rock glaciers (~11.3 km2) in the year 2009. Using a 1990 Landsat scene from this area, we estimated a retreat rate of 26% reduction (~1.4% per year) of the glacier covered area between 1990 and 2009. The minimum elevation of the front talus of active rock glaciers indicates that the lower limit of discontinuous mountain permafrost in the region is located around 2800 m a.s.l. The results here provide new information about the current extent and recent behavior of glaciers and the spatial distribution of mountain permafrost in this poorly known region of the southern Andes. The lack of complete, long climate records in the area precludes detailed analyses of the recent response of glaciers to climate variability. However, regional warming trends and a recent reduction in winter precipitation may have contributed to the observed recent glacier wastage in the Domuyo region. Fil: Falaschi, Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Masiokas, Mariano Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de ...